A parenting needs inventory development and validation - Cruz, Francisca Lomotan
As an answer to the lack of intervention program based on the needs of parents in the Philippines, the study has developed and validated an inventory which assesses parenting needs along four dimensions, namely: knowledge, family management, interpersonal relations, and personal problems.